Membongkar Privasi: Pengungkapan Gugatan Perceraian di Media Sosial - Roulinta Yesvery Sinaga (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2024)
The disclosure of divorce petition reasons on social media is often presented in written form. Divorce issues can become headlines in mass media, characterized by subjective perspectives from informants or sources explaining the reasons for the divorce. The viral divorce issue of Ria Ricis and Teuku Ryan on the Instagram account